Selection of a Surgical Approach for Total Hip Arthroplasty According to the Depth to the Surgical Site. Issue 3 (May 2017) - Ohmori, Takaaki; Kabata, Tamon; Maeda, Toru; Kajino, Yoshitomo; Taga, Tadashi; Hasegawa, Kazuhiro; Inoue, Daisuke; Yamamoto, Takashi; Takagi, Tomoharu; Tsuchiya, Hiroyuki
Background: The surgical depths of approaches for total hip arthroplasty (THA) have not been reported previously. In this study, we investigate the relationships between the distances to the centre of the femoral head in different approaches and body mass index (BMI). Methods: The study included patients with normal hip joints who presented to our hospital. We used the pelvic coordinate system relative to the anterior pelvic plane and the femur coordinate system relative to the posterior condylar plane. We assessed the anterior, anterolateral, lateral and posterior approaches, and defined each approach line. We evaluated each distance in terms of BMI and gender. Results: 164 hips were assessed. The distance to the centre of the femoral head was the longest in the posterior approach, followed by the lateral, anterolateral, and anterior approaches (p<0.05). Additionally, the distance in each approach increased as patients' BMI increased. The approximated line tilts were almost the same. The correlation coefficients between BMI and the distance to the centre of the femoral head were high in all approaches. In the anterior and anterolateral approaches, men with low BMI had a short distance to the femoral head. The distance for each approach was measured according to the pelvic coordinate system and the femur coordinate system. The results showed no significant differences between them. Conclusions: The distance to the centre of the femoral head is the shortest in the anterior approach, regardless of BMI and gender. The distance in each approach might increase with an increase in BMI. BMI has similar effects in all approaches.